2012
DOI: 10.1007/s11033-012-1722-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress markers in pathogenesis of diabetic neuropathy

Abstract: Experimental evidences suggest that hyperglycaemia-induced overproduction of reactive oxygen species and subsequent damage to proteins, lipids and DNA may play a key role in the development of distal symmetric polyneuropathy (DSPN)—the most common complication of diabetes mellitus. The study population consisted of 51 individuals aged 52–82 years classified into 3 groups: 16 patients diagnosed with type 2 diabetes mellitus (T2DM) with DSPN, 16 T2DM patients without DSPN and 19 control subjects without diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 60 publications
6
86
1
2
Order By: Relevance
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower values of reduced glutathione and reduced glutathione/oxidized glutathione ratio in association with DSPN have been reported [69]. Lower plasma concentrations of nitric oxide and higher endogenous oxidative DNA damage in T2D patients with DSPN have also been observed [70]. Bierhaus et al have reported increased plasma methylglyoxal concentrations in association with painful DSPN [71].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, in a recent clinical study, TAC was not significantly decreased even in the presence of SOD and GPX depletion [63]. It is possible that this discrepancy could be due to different clinical stages of the patients from the two studies.…”
Section: Hyperglycemia As the Great Villain In Diabetes Mellitus: Indmentioning
confidence: 81%
“…In research conducted by Takuma et al it was shown that blocking RAGE receptors in mice resulted in reduced frequency of nerve complications [21]. Oxidative stress, which is greatly increased in diabetes, is currently considered an important factor in pathogenesis of gastrointestinal complications [9,22]. Disorders in hexosamine and protein kinase C (PKC) transformation pathways also play an important role in RONS production [7].…”
Section: Pathogenesismentioning
confidence: 99%